PENGARUH SUPERVISI AKADEMIK DAN MANAJEMEN KELAS TERHADAP EFEKTIVITAS PEMBELAJARAN DI SD - Lydia Puspita; Tri Widayatsih; Mahasir Mahasir (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The effectiveness of learning in public elementary schools in Kalidoni District, Palembang, still shows significant variation between schools, as reflected in the uneven academic achievements of students, even though access to basic education has been quantitatively achieved. This problem is triggered by academic supervision practices that tend to be administrative and lack reflection, as well as suboptimal classroom management in creating a conducive learning environment, such as monotonous room arrangements and a lack of interactive teaching aids, thereby hampering teacher performance and holistic student achievement. This study aims to analyze the partial and simultaneous effects of academic supervision and classroom management on learning effectiveness. Using a quantitative approach, a sample of 86 teachers was taken from a population of 515 teachers from 28 public elementary schools via cluster random sampling; data were collected through Likert scale questionnaires, observations, and documentation, then analyzed using multiple linear regression. The results show that academic supervision has a significant positive effect of 46.3%, classroom management 38.7%, and simultaneously both contribute 61.5% to the increase in learning effectiveness. The conclusion states that increasing learning effectiveness requires a continuous academic supervision system and adaptive student-oriented classroom management practices to optimally support the quality of basic education ABSTRAK Efektivitas pembelajaran di SD Negeri se-Kecamatan Kalidoni, Palembang, masih menunjukkan variasi signifikan antar sekolah, sebagaimana tercermin dari capaian akademik siswa yang tidak merata, meskipun akses pendidikan dasar telah tercapai secara kuantitatif. Masalah ini dipicu oleh praktik supervisi akademik yang cenderung administratif dan kurang reflektif, serta manajemen kelas yang belum optimal dalam menciptakan lingkungan belajar kondusif, seperti penataan ruang yang monoton dan kurangnya alat peraga interaktif, sehingga menghambat kinerja guru dan pencapaian holistik siswa. Penelitian ini bertujuan menganalisis pengaruh parsial dan simultan supervisi akademik serta manajemen kelas terhadap efektivitas pembelajaran. Menggunakan pendekatan kuantitatif, populasi 515 guru dari 28 SD Negeri diambil sampel 86 guru via cluster random sampling; data dikumpul melalui angket skala Likert, observasi, dan dokumentasi, lalu dianalisis dengan regresi linier berganda. Hasil menunjukkan supervisi akademik berpengaruh positif signifikan sebesar 46,3%, manajemen kelas 38,7%, dan secara simultan keduanya menyumbang 61,5% terhadap peningkatan efektivitas pembelajaran. Kesimpulan menyatakan bahwa peningkatan efektivitas pembelajaran memerlukan sistem supervisi akademik berkelanjutan dan praktik manajemen kelas adaptif yang berorientasi siswa untuk mendukung mutu pendidikan dasar secara optimal.